2021
DOI: 10.1123/ijatt.2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

The Star Excursion Balance Test: An Update Review and Practical Guidelines

Abstract: The Star Excursion Balance Test (SEBT) is a reliable, responsive, and clinically relevant functional assessment of lower limbs’ dynamic postural control. However, great disparity exists regarding its methodology and the reported outcomes. Large and specific databases from various population (sport, age, and gender) are needed to help clinicians when interpreting SEBT performances in daily practice. Several contributors to SEBT performances in each direction were recently highlighted. The purpose of this clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 54 publications
3
37
0
7
Order By: Relevance
“…Balance tests (e.g., one-legged stance) are frequently used to quantify balance performance. For the purpose of standardization, the use of arm movement is often limited during test execution (Gribble et al, 2012 ; Picot et al, 2021 ). For example, the arms are fixed at the hips or placed flat across the chest.…”
Section: Introductionmentioning
confidence: 99%
“…Balance tests (e.g., one-legged stance) are frequently used to quantify balance performance. For the purpose of standardization, the use of arm movement is often limited during test execution (Gribble et al, 2012 ; Picot et al, 2021 ). For example, the arms are fixed at the hips or placed flat across the chest.…”
Section: Introductionmentioning
confidence: 99%
“…The composite (COM) reach distance was calculated as the sum of three directions divided by three times the length of the lower limbs and then multiplied by 100. Previous studies demonstrated high interrater reliability in the assessment of the mSEBT reach distances [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the systematic review by Gribble et al (2012) provides recommendations for the most reliable procedure, various protocols have been described in the literature. Recent practical guidelines emphasize the need for consistent procedures (Picot et al, 2021). The most common and reliable method requires four practice trials in the ANT, PM, and PL directions followed by three recorded trials on each leg.…”
Section: Star Excursion Balance Testmentioning
confidence: 99%
“…The distance is recorded (in cm) and evaluated in relation to the limb length (from the anterior and superior iliac spine to the medial malleolus). As recently discussed by Picot et al (2021) everal foot positions have been also described during the test and could result in significant misinterpretation when comparing studies. The most commonly used procedure, especially in large cohorts, is described with the most distal aspect of the big toe at the intersection of the three directions.…”
Section: Star Excursion Balance Testmentioning
confidence: 99%